Exploring the impact of massive open online courses on enhancing intercultural communication competence: A systematic literature review - Dejuan Mao; Fathiyah Mohd Kamaruzaman; Ahmad Zamri Mansor (Environment and Social Psychology, 2025)
With the rapid advancement of globalization, intercultural communication has become increasingly essential in political, economic, and cultural contexts. In this context, online learning has emerged as a key avenue for fostering Intercultural Communication Competence (ICC), as it overcomes constraints of time, location, cost, and eligibility, promotes the sharing of high-quality courses and advances educational equity. However, currently limited research has systematically explored how ICC can be effectively cultivated through MOOCs, especially based on empirical evidence. To address this gap, this study aims to explore the relationship between MOOCs and ICC through a Systematic Literature Review (SLR). The review analyzes selected articles retrieved from Scopus, Web of Science (WoS) and Education Resources Information Center (ERIC) using predefined inclusion and exclusion criteria. The findings show that authentic task-driven learning, technology-supported interaction, and experiential learning are key pathways to enhancing ICC. By breaking down geographical and cultural barriers and offering authentic tasks within intercultural communication environments, MOOCs provide students with effective opportunities to enhance their ICC through the integration of practical, culturally interactive learning tasks. This study concludes that MOOCs have significant potential in enhancing ICC within higher education. The insights derived from this review may guide future research and practice in integrating ICC-focused strategies into online learning environment.